2020
DOI: 10.15386/mpr-1581
|View full text |Cite
|
Sign up to set email alerts
|

Occupation-related musculoskeletal disorders among dental professionals

Abstract: Background and aim. Dentists are exposed to a wide range of work-related factors that may result in various occupational diseases of which musculoskeletal disorders (MSDs) are common. The purpose of this study was to determine the prevalence and distribution of MSDs among dental professionals of our institution and to compare the prevalence of MSDs among the various dental specialists. Methods. A self-administered questionnaire, which included basic demographic details, work experience in dentistry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 11 publications
(21 reference statements)
1
35
1
1
Order By: Relevance
“…There is broad evidence of an association between work-related MSDs [ 2 ] and the dentistry profession [ 3 , 4 , 5 , 6 , 7 ]. The occurrence of MSDs among dentists varies between 47% and 93% in different studies [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Several studies among dentistry students showed the early onset of MSDs even during the undergraduate studies, where the occurrence ranged from 39% to 93% [ 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is broad evidence of an association between work-related MSDs [ 2 ] and the dentistry profession [ 3 , 4 , 5 , 6 , 7 ]. The occurrence of MSDs among dentists varies between 47% and 93% in different studies [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Several studies among dentistry students showed the early onset of MSDs even during the undergraduate studies, where the occurrence ranged from 39% to 93% [ 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies compared actual students in different years of dentistry studies. In all the studies, women suffered from MSDs more often than men [ 3 , 8 , 9 , 14 , 15 , 16 , 20 , 23 , 25 , 26 , 27 , 28 , 29 , 34 , 35 , 36 ]. The most frequent areas of pain are neck, lower back, shoulders and hands [ 3 , 7 , 14 , 15 , 16 , 17 , 19 , 20 , 23 , 24 , 26 , 27 , 28 , 29 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies show that number of dentists suffering from MSDs seek professional help, take sick leave from respective institutes, change their work setting or reduce their working hour [24][25][26]. Indian studies reported that 13.9% -47% dentists sought professional help, 35% used medication for symptomatic relief and 12% used physiotherapy [27,28]. According to a local study 40.7% of dental practitioners sought medical treatment and only 16% dentists and 11% dental students took sick leave [29].…”
Section: Resultsmentioning
confidence: 99%
“…One-third of dentists are obese and 60% have low back pain. Sixty percent stated that they were tense, tense, or depressed, and 48.6% had difficulty sleeping 18 . In another study conducted in Brazil, it was concluded that the incidence of low back pain in dentists is higher than the general population 3 .…”
Section: Discussionmentioning
confidence: 99%